Çağdaş Kural Dışı Tekfirciliğin Yapısal Unsurları Üzerine Bir Model Denemesi - III - (:unkn) unknown (My University, 2016)
Makalede dört örnek kişiden hareketle çağdaş tekfirciliğin sosyal kimliği ele alınmaktadır. Gözlem altına alınan örnekler, genel bir profilden ziyade, itibari değerlendirmelere izin vermektedir. Buna göre, sosyal cinsiyet bakımından tekfircilik erkek egemen bir harekettir, kadınlar grup faaliyetlerinde önde değildirler. Yirmili yaşların ortalarında belirginleşen tekfirci eğilimler yaş ilerledikçe azalmaktadır. Çağdaş tekfirciliğin çatışma bölgelerinde şekillenen bir ideoloji olduğu görülmektedir. Resmi din eğitiminden gelmeyen tekfirciler, çeşitli dini gruplar içinde kendi kimliklerini bulmaktalar ve İslâmî hareketlerde öne çıkarılan külliyatlardan özel okumalara dayalı yorumlarla tekfiri çizgiye kaymaktadır. Sınıfsal olarak alt-orta gelir grubuna mensupturlar. Dava işleri dışında ya ek/yan işleri ya aileden mülkleri vardır ya da grup içi bağış ekonomisine dayalı gelirleri vardır. Çatışma bölgeleriyle ilişkileri, kendilerini askeri kamplara, dolayısıyla silaha aşina kılmakla birlikte; modern tekfircilerin, umumiyetle, ideolog vazifesi gördükleri, fikirlerinden etkilenen dış halkaların şiddete daha meyyal oldukları görülmektedir.

This article deals with the social identity of contemporary takfiris based on the four distinctive cases as the last chain of our series about the problem. These cases provide a general explanation of the modern takfirists, rather than a try to put forward a typology. From the cases observed in this article, in terms of social gender, takfir is a masculine movement and women are not in the forefront within the group activities. Takfiris are generally persons who are in their mid-twenties, and there is a contrasting relationship between takfir and age; as age increases tendency towards takfiri belief diminishes. In terms of geography, modern takfir has been shaped in the conflicting areas among the Muslim countries. Lacking regular and official religious education, takfiris get closer to the takfir line by special reading and interpretations from the anthology of Islamic movements. In terms of economy, they reflect the lower and middle classes. Beside "dava" activities, there are some possibilities of their economic situations. They can have an extra economic activity/job, properties handed down from parents or donations from inner-group relations. Having connections with the conflict areas in the Islamic world or socializing in those cultural spheres familiarizes them with arms and violence; however, the cases here show that they are ideologues who affect outer circles inclined towards terror and violence.
A Model for the Structural Elements of Contemporary Takfir Discourse-III
Keywords: Din Bilimi